Group Reality Therapy untuk mereduksi kecemasan narapidana wanita dalam menghadapi respon sosial menjelang masa pembebasan bersyarat - Hanum Nindialoka (Universitas Muhammadiyah Malang, 2021)
Prisoners when facing the period of parole are certain to experience anxiety problems because of the negative stigma and social responses.The purpose of this case study is to reduce the prisoners’s anxiety symptoms by using Group Reality Therapy. The assessment method uses semi-structured interviews, observation, and the TMAS (Talyor Manifest Anxiety Scale) scale. The subjects were four inmates, male aged 22-23 years. The results of the assessment showed that the anxiety problems experienced by the subjects were at a moderate level of anxiety. Analysis by comparing before and after psychological intervention. The results of psychological intervention using Group Reality Therapy showed a decrease in anxiety symptoms.